Edukasi Bahaya Cyberbullying di Kalangan Remaja Guna Membangun Kesadaran dan Ketangguhan Digital di SMKN 1 Kaligondang - Purwono, Purwono; Hadi Jayusman; Safa Kiana; Fakhri Zahi Mumtaza (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2025)
Cyberbullying has become a major challenge that affects the mental health of adolescents in the digital era. This community service program aims to increase awareness and digital resilience of SMKN 1 Kaligondang students through education about the dangers of cyberbullying. Using counseling methods, interactive discussions, and case simulations, this program helps increase students' awareness of various forms of cyberbullying, including its psychological and social impacts, as well as strategies for preventing and handling cyberbullying wisely. The results of the activity showed an increase in students' understanding of the risks of cyberbullying, as well as a better understanding of how to report and deal with such situations in cyberspace. In addition, students showed a greater commitment to maintaining digital ethics and practicing safe social skills in digital media. This article is expected to be a basis for schools in developing similar initiatives to form a generation that is more aware and resilient in dealing with cyberbullying